2006
DOI: 10.1111/j.1440-1681.2006.04355.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF CASTRATION ON CANNABINOID CB1 RECEPTOR EXPRESSION AND ON THE BIOLOGICAL ACTIONS OF CANNABINOID IN THE PAROTID GLAND

Abstract: In the present study, we examined whether cannabinoid receptor expression and the effects of receptor stimulation vary as a function of gonadal status in a peripheral tissue, namely the male rat parotid gland. Four groups of male rats were studied: gonadal intact, castrated, castrated testosterone (1 mg/100 g bodyweight) treated and gonadal intact testosterone treated. 2. The results showed that the density of CB(1) receptors decreased after castration and that receptor density was restored to control values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This study confirms the presence of the CB1 receptor in the major salivary glands of dogs and that CB1 localizes to the cells of striated ducts, as previously demonstrated in rats (Prestifilippo et al 2006;Busch et al 2006). The immunohistochemical positive reaction inside the cells was localized on or near to the apical membrane.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirms the presence of the CB1 receptor in the major salivary glands of dogs and that CB1 localizes to the cells of striated ducts, as previously demonstrated in rats (Prestifilippo et al 2006;Busch et al 2006). The immunohistochemical positive reaction inside the cells was localized on or near to the apical membrane.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, interest in these substances has increased as a consequence of the cloning of two receptors specific to cannabinoids, cannabinoid receptor type 1 (CB1) and CB2, in humans (Munro et al 1993) and laboratory animals (Matsuda et al 1990), and the discovery of endogen substances, commonly indicated as endocannabinoids (Busch et al 2006), that bind to these receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, limited evidence supports the possible effects of testosterone on potentiating the action of cannabinoid type 1 receptor agonists on presynaptic inhibition of excitatory inputs in vitro 57 and on transcriptional up-regulation of the CNR1 gene. 58,59 …”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones during the estrous cycle have been linked with brain CB 1 receptor density, which is reduced in the limbic forebrain and hypothalamus after ovariectomy and castration but can be restored after estradiol, progesterone, and testosterone administration in intact and ovariectomized/castrated rats (8084). High levels of stress-induced corticosteroid secretion and base-line corticosteroids as well as slow clearance of corticosteroids could lead to reduced CB 1 receptor levels in stressed females (85, 86).…”
Section: Discussionmentioning
confidence: 99%